Food Security for Community-Based Tourism of Koh Phithak Lang Suan District, Chumphon Province - Na Thongkaew, Benjamas; Ruksapol, Amnat; Monpipath, Kasinee; Buaurai, Sarunya; Tokeree, Weeraporn; Morasilp, Patida (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
This research aimed to study the model of food security of the tourist area by the community of Koh Phithak, Lang Suan District, Chumphon Province. Data was collected, using 200 questionnaires and 17 interviews with villagers. The results of the study were divided into 2 parts. For the first part of results about the perception of the living status of people in the community, the findings showed that local home sourced ingredients used to serve tourists from the local fishery. Garden vegetables from the market Self-cultivation for household consumption and community members has equal rights for food. In accordance with the tourists perception, seafood from the community is fresh and clean (mean = 4.65), and positive perception of food security is the most satisfactory (mean = 4.35), Diversity and taste (mean = 4.33). For the second part of results about the food security awareness, the findings also indicated that the community was aware about the reduced amount of sea animal, therefore food security activities were set up such as building a fish farm using coconut leaves, using EM balls to filter the water and removing trash along with the coral reef. Consequently, successful factors of food security were to increase the number of sea animals grouping to maintain strong marine resources, to support communities in generating more income by adopting food processing.